The effect of growth hormone deficiency on inflammatory markers in Sheehan's syndrome - Alay, Murat; Yildiz, Saliha; Sakin, Aysegul; Miyase Sonmez, Gulcin (Annals of Medical Research, 2021)
Aim: Mean platelet volume (MPV), lymphocyte count (LC), neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) are currently gaining interest as new markers of inflammation and independent risk factors for cardiovascular diseases. The aim of this study was to evaluate the effect of growth hormone (GH) deficiency on MPV, NLR, and PLR values in patients with Sheehan’s syndrome.Materials and Methods: 23 women with Sheehan’s syndrome (SS), and 30 healthy women as control group were included in the study. The study was performed retrospectively. Demographic and clinical characteristics, hormone and haematological parameters of subjects were evaluated. MPV, NLR, PLR and LC values were compared between two groups.Result: The mean age of SS and control groups were 53.1 ± 11.1 and 55.1 ± 10.5 years, respectively. MPV, PLR, NLR were lower and LC was higher in SS group than the control group. (p = 0.010, 0.033, 0.017, 0.010 respectively). A significant positive correlation was found between insulin-like growth factor1 (IGF1) and MPV, PLR in the SS group (p = 0.003 r: 0.62, p: 0.033 r: 0.46). Conclusion: MPV, NLR, PLR were lower and LC was higher in SS group compared to control group. There was a significant positive correlation between IGF1 and MPV, PLR in the SS group. These results showed that growth hormone deficiency led to a decrease in some inflammatory markers such as MPV, NLR, PLR. Increased LC in these patients may indicate inflammation.
Keywords: Mean platelet volume; neutrophil to lymphocyte; sheehan syndrome